2016
DOI: 10.1177/0020764015623971
|View full text |Cite
|
Sign up to set email alerts
|

Socially restrictive attitudes towards people with mental illness among the non-psychiatry medical professionals in a university teaching hospital in South India

Abstract: Socially restrictive attitudes towards people with mental illness are prevalent among substantial number of medical professionals in a low-income country like India. Personal acquaintance with people who have mental illness appears to be the only significant factor that reduces medical professionals' socially restrictive attitudes towards them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
0
17
1
1
Order By: Relevance
“…Besides widespread stigma in the general community, studies have also found nonpsychiatric healthcare and paramedical personnel to have stigmatizing attitudes against those with mental illnesses. [171819] Although in our study there was no significant association between perceptions of stigma and family history of mental illness or contact with someone else with a mental illness, one survey from a teaching hospital among nonpsychiatric medical professionals also found that social contact with an affected person was associated with less socially restrictive attitudes. [17] In view of this barrier of stigmatizing attitudes among healthcare workers, an interventional study aimed at reducing stigma through targeting nonspecialist healthcare workers is being planned in low-resource settings in Nepal.…”
Section: Discussioncontrasting
confidence: 69%
“…Besides widespread stigma in the general community, studies have also found nonpsychiatric healthcare and paramedical personnel to have stigmatizing attitudes against those with mental illnesses. [171819] Although in our study there was no significant association between perceptions of stigma and family history of mental illness or contact with someone else with a mental illness, one survey from a teaching hospital among nonpsychiatric medical professionals also found that social contact with an affected person was associated with less socially restrictive attitudes. [17] In view of this barrier of stigmatizing attitudes among healthcare workers, an interventional study aimed at reducing stigma through targeting nonspecialist healthcare workers is being planned in low-resource settings in Nepal.…”
Section: Discussioncontrasting
confidence: 69%
“…Stigma in mental health poses a significant barrier to recovery and social inclusion. 7 Although early intervention in psychiatric illness is associated with improved health outcomes, 8 stigma has been found to inhibit help-seeking behaviour. 9 Stigma in mental health is an independent predictor of poorer outcomes after controlling for the initial severity of symptoms and disability.…”
mentioning
confidence: 99%
“…Uganda, South Africa, Nigeria, Nepal, India and Ethiopia), where negative attitudes of service providers towards people with mental illness was identified as an important supply-side barrier to seeking mental health care across all countries [30]. Similarly, a study conducted with medical professionals (faculty members and postgraduate trainees) in Southern India reported that a significant number of the medical professionals had negative attitudes towards people with mental illness [32].…”
Section: Discussionmentioning
confidence: 99%